From teachers to global educators: the Malaysian GCED manual - Amir Yazid, Amirah Athirah; Syed Abdullah, Syed Mohamad; Shaari, Anis; Bazlan, Anis Shahira (2025)
Global Citizenship Education (GCED) is gaining global recognition as a transformative approach in teacher training, particularly aligned with Sustainable Development Goal (SDG) 4.7, which aims to ensure that all learners acquire the knowledge and skills needed to promote sustainable development, including through education for global citizenship. However, Malaysian teacher training institutions often lack structured and contextualized tools for embedding GCED in instructional practice. This project introduces an innovative product, a manual titled “Pendidikan Kewarganegaraan Global untuk Institusi Pendidikan”, developed by USM’s Global Citizenship Education Cooperation Centre-Malaysia GCC-Malaysia@USM team. The manual integrates UNESCO’s core values of diversity, solidarity, and shared sense of humanity into teacher education, supported by a modular training framework. The manual features a wide range of practical content, emphasizing the integration of three key domains of GCED: cognitive (Head), socio-emotional (Heart), and behavioral (Hand). It includes basic information on understanding GCED, classroom activities, reflective exercises, and planning templates. These are tailored to help teachers bring abstract global issues such as diversity, sustainability, peace, human rights, and global interdependence into relatable classroom experiences. All these were implemented through structured sessions across several teacher training institutes in Malaysia. Findings demonstrate an increase in reflective practice, global awareness, and classroom integration of GCED concepts among participating teachers. This project strongly contributes to the realization of SDG 4.7 in the Malaysian context and has high scalability potential, positioning Malaysia as a regional leader in operationalising GCED through teacher education in an effort to build educators’ capacity in fostering globally aware and socially responsible students.